Specific characteristics of STEMI in COVID-19 patients and their practical implications: a systematic review. (3rd October 2022) - Gitto, M; Novelli, L; Cozzi, O; Reimers, B; Condorelli, G; Stefanini, G G
Abstract: Introduction: STEMI is one of the cardiac emergencies whose management has been mostly challenged by the COVID-19 pandemic. Patients presenting with the "lethal combo" of STEMI and concomitant SARS-CoV-2 infection have faced dramatic issues related to need for self-isolation, systemic inflammation with multi-organ disease, and difficulties to obtain timely diagnosis and treatment. Methods: We performed a systematic search of three electronic databases from February 1st 2020 to January 31st 2022. We included all studies reporting crude rates of in-hospital outcomes of STEMI patients with concomitant COVID-19. Results: A total of 9 observational studies were identified, mainly conducted during the first wave of the pandemic. STEMI patients with COVID −19 were more likely Afro-American and displayed higher rates of hypertension and diabetes with lower smoking prevalence. Associated comorbidities, including coronary artery disease, prior stroke and chronic kidney disease were also more common in those with SARS-CoV-2 infection. At coronary angiography, a higher thrombus burden in COVID-19 positive STEMI patients was highlighted, with up to 10-fold higher rates of stent thrombosis and greater need for glycoprotein IIb/IIa inhibitors and aspiration thrombectomy; this was not always associated with prolonged times from symptom onset to hospital admission and door-to-balloon. COVID-19 positive STEMI patients were less likely to receive coronary angiography and primary PCI, and more likely to be treated with fibrinolytics only. At the same time, patients with Covid-19 were more prone to present MINOCA. In-hospital mortality ranged from 15% to 40%, with consistent variability across different studies and subjects who tested positive for SARS-CoV-2 did also present higher rates of cardiogenic shock, cardiac arrest, prolonged ICU stay, mechanical ventilation, major bleeding, and stroke. Conclusion: The coexistence of STEMI and COVID-19 was associated with increased in-hospital mortality and poor short-term prognosis. This was not entirely attributable to logistic issues determining delayed coronary revascularization, since patients' specific clinical and angiographic characteristics, including higher burden of cardiovascular risk factors and greater coronary thrombogenicity might have substantially contributed to this trend. Funding Acknowledgement: Type of funding sources: None.